NEMUI NYIMAH: LAMPUNG LOCAL WISDOM WITH RELIGIOUS MODERATION INSIGHT - Syahputra, Muhammad Candra; Ruslan, Idrus (AKADEMIKA: Jurnal Pemikiran Islam, 2021)
Diversity is a characteristic of the Indonesian nation, as well as a treasure of the nation. Differences in ethnicity, religion, race, and between groups are also like a double-edged knife. One side is a one-sided wealth that can cause conflict amid community life. Therefore, religious moderation is important to be grounded as an inclusive religious understanding. Local wisdom is a legacy that is a prerequisite for understanding religious moderation. This study demonstrates an understanding of religious moderation in nemui nyimah as local wisdom in Lampung. This study uses a qualitative approach. In collecting data, the writer conducts interviews and observations for field observations and literature books, journals, and other written sources. The results of this study indicate that local wisdom in nemui nyimah contains religious moderation insights such as tolerance, multiculturalism, pluralism, and humanism to create harmony in people's lives.